2008
DOI: 10.1093/europace/eup006
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of the patients with Brugada type electrocardiogram: a community-based prospective study

Abstract: Clinical presentation is the most important parameter in the risk stratification of patients with Brugada ECG. Programmed electrical stimulation seems valuable, particularly in patients with previous syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 23 publications
4
66
1
3
Order By: Relevance
“…This international registry also contains follow-up data on patients included in a previous study published in 2005 and recently reported Italian patients. 2,8 From the present study comprising 1029 patients, 212 patients were initially described in Circulation in 2005. 2 The follow-up of this population was 40Ϯ50 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This international registry also contains follow-up data on patients included in a previous study published in 2005 and recently reported Italian patients. 2,8 From the present study comprising 1029 patients, 212 patients were initially described in Circulation in 2005. 2 The follow-up of this population was 40Ϯ50 months.…”
Section: Methodsmentioning
confidence: 99%
“…The Italian group included 192 patients in the registry; of them, 166 have also been described in Europace. 8 Finally, 378 of the 1029 patients have already been included in a publication, which means that 657 patients are new. We can consider that over a total follow-up of 1029ϫ37ϭ38 073 months, the patients from the Eckardt publication represent 212ϫ40ϭ8480 months of follow-up, and the patients from the Europace publication from the Italian group represent 166ϫ30ϭ4980 months, for a total of 13 460 months.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4 shows the outcome data in the various studies in which the predictive value of electrophysiological study was tested in asymptomatic patients with a spontaneous type 1 ECG or a drug-induced ECG. 105,106,110,111,[116][117][118][119][120][121][122][123] Indeed, the initial drop in follow-up events in the studies published by Brugada et al 110,116 can only be explained by the inclusion of patients with a more-severe condition. In the more-recent studies, the event rate during a follow-up period of 3 to 4 years is between 0% and 5%, the latter still including the patients already included in the first series published by Brugada et al 123 It is not clear why the results diverge, but the differences in electrophysiology study protocol may be critical.…”
Section: Insight Into Brugada Syndrome An Updatementioning
confidence: 99%
“…The predictive value of EPS in stratifying these patients was also demonstrated by Giustetto et al, who prospectively studied the incidence of arrhythmic events in 166 patients with type 1 Brugada ECG pattern and found that the only predictors were syncope, aborted sudden death and positive EPS. 7 However, according to Priori et al, VT or VF inducibility on EPS did not predict malignant arrhythmias or sudden death, 8 and along the same lines, Gehi et al concluded that EPS did not add relevant information for the management of patients with Brugada syndrome. 9 Furthermore, multivariate analysis of the largest registry of Brugada patients, the FINGER Brugada Syndrome Registry, showed that EPS results were not predictive of time to first arrhythmic event.…”
Section: Discussionmentioning
confidence: 99%